Development of a WordPress-Based Learning Website to Train Students’ Visual Intelligence on Chemical Equilibrium Material - Azizah, Putri Nur; Lutfi, Achmad (Jurnal Paedagogy, 2023)
This research aims to develop a WordPress-based chemistry learning website that can train students’ visual intelligence on chemical equilibrium material. This study used the 4D development model (Define, Design, Develop, and Disseminate), which was limited to the development stage with limited trials conducted in class XI SMAN 1 Cerme Gresik. The instruments used in this study were media validation sheets, practicality questionnaires, student activity observation sheets, and cognitive and visual intelligence learning outcomes test sheets. The data from this study were analyzed descriptively quantitatively, with a validity score ofâ‰¥3, a percentage of practicality obtained â‰¥61%, and the effectiveness analyzed using N-Gain and t-test. The results showed that WordPress-based chemistry learning website media was feasible to use and could train visual intelligence to students. That is because chemistry learning websites have mode four validity, categorized as very valid. Then the percentage of practicality obtained from the student response questionnaire was 96.21% with a very practical category and was measured by observing student activities with relevant activities at meeting 1 of 91.85% and meeting 2 of 90.74% so that the media can be said to be very practical. The effectiveness of the media was measured based on the posttest results with the N-Gain score obtained on cognitive learning outcomes of 0.75 and visual intelligence learning outcomes of 0.73 with a high category so that the website media was said to be effective. Wilcoxon test results showed that cognitive learning outcomes had a significance value of 0.000, and visual intelligence learning outcomes had a significance value of 0.000, indicating a significant variation between pretest and posttest results because of the significant value <0.05.